2007
DOI: 10.1521/soco.2007.25.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Did Everybody Know It All Along? A Review of Individual Differences in Hindsight Bias

Abstract: Hindsight bias has traditionally been regarded in light of general laws of information processing and memory. The current review presents a complementary view of hindsight bias, summarizing research on individual differences in the magnitude of the bias. According to an individual difference perspective, the magnitude of the bias is influenced by individual traits, needs, and motives, and not exclusively the result of rational, if sometimes faulty, information processing. Our review emphasizes those traits tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…In short, the observer participants' hindsight impressions did not have much emotional significance for them. In turn, this underscores the motivational nature of the hindsight effects in the actor-hindsight condition, as is predicted by both the self-blame avoidance and retroactive pessimism views and by the idea of motivated hindsight bias in general (e.g., Campbell & Tesser, 1983;Musch & Wagner, 2007;Pezzo & Pezzo, 2007).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In short, the observer participants' hindsight impressions did not have much emotional significance for them. In turn, this underscores the motivational nature of the hindsight effects in the actor-hindsight condition, as is predicted by both the self-blame avoidance and retroactive pessimism views and by the idea of motivated hindsight bias in general (e.g., Campbell & Tesser, 1983;Musch & Wagner, 2007;Pezzo & Pezzo, 2007).…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, explanations of hindsight bias have focused on biased causal reasoning (e.g., Hawkins & Hastie, 1990;Pezzo, 2003;Roese & Olson, 1996;Wasserman, Lempert, & Hastie, 1991) or biased memory reconstruction processes (e.g., Erdfelder & Buchner, 1998;Pohl, Eisenhauer, & Hardt, 2003;Stahlberg & Maass, 1998). More recent research, however, has emphasized that self-related motivational processes play a major role in it as well (for overviews, see Musch & Wagner, 2007;Pezzo & Pezzo, 2007;Renner, 2003). This becomes most obvious when hindsight judgments are made regarding event outcomes that have some emotional significance for the self and invoke self-defensive processes (see Sedikides & Gregg, 2008, for a recent overview of self-related motivational processing).…”
mentioning
confidence: 99%
“…Another consideration when evaluating how much to disclose is that of hindsight bias, the tendency of individuals to overestimate the predictability of an outcome via the assimilation of new information (Musch & Wagner, 2007). Hindsight bias could be at work in a number of ways when it comes to disclosure in Atkins cases.…”
Section: Information Processingmentioning
confidence: 99%
“…Although hindsight bias is a widely studied phenomenon, few studies have examined individual differences in this bias (Musch & Wagner, ). An early study found that hypothetical and memory hindsight biases were positively correlated across participants, and that a combined memory and hypothetical hindsight bias index was positively correlated with social desirability and motivation for predictability (Campbell & Tesser, ).…”
mentioning
confidence: 99%
“…Similarly, expert baseball players displayed a smaller hindsight bias than novices in recollecting the predicted outcomes of their swings in a memory design (Gray, Beilock, & Carr, ). A memory design computer simulation of hindsight bias demonstrated that there was a smaller hindsight bias among people with more domain‐specific knowledge (Hertwig, Fanselow, & Hoffrage, ), whereas one hypothetical design study (described by Musch & Wagner, ) showed that chocolate experts demonstrated a larger hindsight bias than novices when judging the amount of cocoa in a piece of chocolate, and another showed that self‐rated wine knowledge was unrelated to hindsight bias in judgments about the sweetness of wine (Pohl, Schwarz, Sczesny, & Stahlberg, ). These conflicting findings suggest that additional research on the role of expertise in hindsight bias (in particular, its relation to different components of hindsight bias) is needed.…”
mentioning
confidence: 99%